2016
DOI: 10.1128/aem.01018-16
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of myo -Inositol by Legionella pneumophila Promotes Infection of Amoebae and Macrophages

Abstract: Legionella pneumophila is a natural parasite of environmental amoebae and the causative agent of a severe pneumonia termed Legionnaires' disease. The facultative intracellular pathogen employs a bipartite metabolism, where the amino acid serine serves as the major energy supply, while glycerol and glucose are mainly utilized for anabolic processes. The L. pneumophila genome harbors the cluster lpg1653 to lpg1649 putatively involved in the metabolism of the abundant carbohydrate myo-inositol (here termed inosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 78 publications
1
33
0
Order By: Relevance
“…It is noteworthy that myo-inositol catabolism confers a fitness advantage to Legionella pneumophila in macrophages and amoebae, and that σ S has a positive effect on expression of the iol operon and myo-inositol uptake 48 . It is possible that expression of the Salmonella prp , iol and fuc genes is activated in vivo by σ S and provides fitness advantages to the pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that myo-inositol catabolism confers a fitness advantage to Legionella pneumophila in macrophages and amoebae, and that σ S has a positive effect on expression of the iol operon and myo-inositol uptake 48 . It is possible that expression of the Salmonella prp , iol and fuc genes is activated in vivo by σ S and provides fitness advantages to the pathogen.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro data have shown that infection of macrophages by some intracellular bacteria is enhanced by their ability to use myo-inositol as an energy source. 25 An additional issue for this trial was its suspension when particulates (later identified as glass lamellae) were found in the third lot of drug, which was never used. Glass (27) Pulmonary hemorrhage 5/50 (10) 7/33 (21) Necrotizing enterocolitis 9/50 (18) 5/33 (15) Spontaneous gastrointestinal perforation 5/50 (10) 5/33 (15) Immaturity 4/50 (8) 5/33 (15) Bronchopulmonary dysplasia 6/50 (12) 2/33 (6) Other infection 6/50 (12) 0 Pulmonary hypoplasia 0 3/33 (9) Pneumonia 2/50 (4) 0 Congenital malformation 1/50 (2) 1/33 (3) Multiple organ failure 0 1/33 (3) Hepatic failure or cirrhosis 0 1/33 (3) Patent ductus arteriosus 0 1/33 (3) Any other cause of death 11/50 (22) 7/33 (21) a There may have been more than 1 primary or contributing cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…This gene was also not found in the genomes of other bacterial strains capable of myo-inositol catabolism such as Clostridium perfringens, Legionella pneumophila, and Enterobacter aerogenes. It is possible that the iolJ gene is replaced by a yet annotated aldolase gene (Berman & Magasanik, 1966;Kawsar, Ohtani, Okumura, Hayashi, & Shimizu, 2004;Manske, Schell, & Hilbi, 2016). impossible to obtain enough cell mass to perform enzymatic assays for RuBisCO activity.…”
Section: Central Metabolismmentioning
confidence: 99%